2021
DOI: 10.1108/ijge-06-2021-0085
|View full text |Cite
|
Sign up to set email alerts
|

Social media's impact on the empowerment of women and youth male entrepreneurs in Egypt

Abstract: PurposeThis study aims to examine the impact of social media (SM) on the creation of digital entrepreneurship by female (irrespective of age) and youth male (aged 18–29 years) entrepreneurs, investigate if SM empowers those entrepreneurs and compare the empowerment characteristics between female and youth male entrepreneurs before and after starting their businesses.Design/methodology/approachSelf-assessment questionnaires were collected from a sample of 408 Egyptian female and youth male digital entrepreneurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The latter is particularly interesting given the skyrocketing usage of SM in Egypt in the past few years (Kemp, 2022). Recent studies have examined the impact of SM use on MSMEs performance (Fakhreldin et al, 2020(Fakhreldin et al, , 2023, on the formation of informal online businesses/digital entrepreneurship (Miniesy et al, 2022) and on women and young male entrepreneurs' empowerment (Beninger et al, 2016;Miniesy et al, 2021), however, no studies have examined its impact on formalisation, which highlights a research gap that this study intends to fill.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The latter is particularly interesting given the skyrocketing usage of SM in Egypt in the past few years (Kemp, 2022). Recent studies have examined the impact of SM use on MSMEs performance (Fakhreldin et al, 2020(Fakhreldin et al, , 2023, on the formation of informal online businesses/digital entrepreneurship (Miniesy et al, 2022) and on women and young male entrepreneurs' empowerment (Beninger et al, 2016;Miniesy et al, 2021), however, no studies have examined its impact on formalisation, which highlights a research gap that this study intends to fill.…”
Section: Introductionmentioning
confidence: 95%
“…But after the start and the operation of the online business this might change. Miniesy et al (2021) showed that informal digital entrepreneurship empowers females and young males in terms of increasing their self-esteem, self-confidence, self-efficacy, autonomy and confidence in their business abilities. In theory, these empowerment traits could boost the entrepreneur's perception of their ability to perform the action (formalise) and could thus encourage formalisation.…”
Section: Formalisation Of Msmes In Egyptmentioning
confidence: 99%
See 1 more Smart Citation
“…This new business environment attracts female entrepreneurs in the Middle East to create various online communities to empower their counterparts and capitalize on the fast, low-cost, and fluid nature of social media platforms. All these aspects facilitate facing many challenges of starting a business [7]. Although women nearly constitute half of the population in Egypt, they are ill-represented in the labor force by only 18.7% in 2020 [8].…”
Section: Introductionmentioning
confidence: 99%
“…For female entrepreneurs in emerging economies, the importance of SM platforms increases as weak ties are created by these platforms to support women in these communities to overcome the pressure of their families' responsibilities and perceived gender roles [7,16]. Prior studies have examined the relationship between social capital and opportunity recognition in the face-to-face context [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%